Finite element and analytical modelling of PVC-confined concrete columns under axial compression - Isleem, Haytham F.; P, Jagadesh; Ahmad, Jawad; Qaidi, Shaker; Althoey, Fadi; Najm, Hadee Mohammed; Sabri, Mohanad Muayad Sabri (Frontiers in Materials, 2022)
Confined concrete in pipes provides a solution for the structures to resist lateral forces and avoids the problems associated with production of confined concrete and lateral reinforcement. To evaluate the influence of PVC pipe on the compressive behavior of concrete filled composite tubes, ABAQUS software was used to simulate 44 concrete filled PVC pipes (CFPT). The influence of internal steel reinforcement, unconfined concrete strength, slenderness ratio, specimen’s size and thickness of PVC tube on failure mode load carrying capacity, and strain of PVC confined reinforced concrete column was studied. The present discussion show that the existing analytical models failed to capture the effect of these parameters. On the other hand, the proposed finite element (FE) models achieve a very good agreement between the experimental and analytical values. The proposed FE model can provide an acceptable portrayal of the CFPT’s response. The response of confined concrete was estimated using trial and error approach and as a result a model for the strain of confined concrete was proposed. The effect of these parameters on the CFPT leads to development of analytical models.